O cotidiano das posses de hip hop em Maceió : territorialidades, visibilidades e poder - Santos, Sérgio da Silva (2014)
The research presents a discussion on the role of Hip Hop Posses in Maceió-Alagoas, and what strategies developed and implemented by these youth organizations on the everyday struggle and search visibility. This work brings some dimensions of interactions practiced by individuals belonging to posses and their lifestyles, as well as the aspects related to identity, spatiality and dynamics of reframing embedded in the core practices of groups. The study was aimed to outline the dimensions of power faced by these groups, especially in relation to the dimensions of territoriality and spatiality in the actions.